Outcomes of Pregnant Females Presented with Non-Reactive CTG - Uzma Ali Memon, Tahmina Mahar, Hina Amanullah, Sabahat Fatima, Sameena, Mahjabeen, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: One of the objectives of this research was to determine the rate outcomes for patients who first presented with non-reactive cardiotocography. Study Design: Descriptive study Place and Duration: Sindh Government Qatar Hospital Orangi town Karachi. Jan 2022-Dec 2022 Methods: 133 women between the ages of 20 and 42 who presented to the OPD or ER with labor pains were included in the research. Abnormalities were seen on both the antepartum and intrapartum CTG. The manner of delivery was decided after a CTG and physical assessment. SPSS 24.0 was used to analyze and input the data. As a follow-up to the stratification process, Chi-square was employed. Values of p less than 0.05 were considered significant. Results: Mean age of the females was 27.14±12.88 years and had mean BMI 36.2±5.81 kg/m2. Mean gestational age of the females was 37.2±3.34 weeks. There were 80 (60.2%) cases had rural residency. Frequency of obesity and anemia was 13 (9.8%) and 18 (13.5%). We found C-section in 58 (43.6%) cases, induction of labor in 42 (31.6%) cases and prolong labor in 33 (24.8%) cases. Frequency of pre-eclampsia found in 46 (34.6%) cases, gestational diabetes in 55 (41.4%) cases and post-partum haemorrhage in 77 (57.9%) cases. Low apgar score found in 25 (18.8%) cases. Conclusion: Cardiotocography monitoring in labor is associated with a higher risk of caesarean sections because of its high false positive rate. Our research shows that pregnant women who are overweight have an increased risk of developing diabetes, premature labor, and preeclampsia and these are contributing factors for non-assuring CTG. Keywords: Non-reactive cardiotocography, C-section, Obesity, Anemia, PPH